Meio e mensagem: usos e apropriações do smartphone nas interações cotidianas de jovens universitários - Moura, Diocsianne Correia de (2014)
The smartphone is now very present in the daily lives of young people, who make uses and appropriations of their tools, transforming it into a new and / or interaction and sociability in the experiences and feelings among users sharing space interface device. The concepts of youth, mobile technology, social life, belonging, identity, consumption, conversation and interaction are used as the theoretical framework of this study. An analysis of this scenario, as noted by researchers in academia, such as Winocur (2009 ) and Castells (2007 ) - with the approaches of cultural, social and intimate relationships established with smartphones, as well as issues of interaction via cell - serves as a reference to observe the progress that is yet to come in regard to mobile technology , given that rare cultural phenomena privacy settled in society and met all its sectors, in such a short time and amplitude, and the advancement and development of these technologies. This study, based on qualitative and quantitative methods, data sought to reveal how to give the best uses and appropriations of the smartphone - the relationship of young people with the handset - and the existence and delineation of changes in their way of life in their social identity mediated through this mobile platform conversation. The data collected partially revealed the universe of uses and appropriations that young people carry on with their everyday smartphone. Analyses permeated the university setting, revealing fragments on the social interaction and the experiments performed by use of the device , especially among university students aged between 25 and 30 years, in Curitiba (PR).